The Impact of Scholarships on Student Achievement: A Mix Methods Study - Gigih Adjie Byantoro; Dewie Tri Wijayati Wardoyoe; Karwanto; Amrozi Khamidi; Mochamad Nursalim (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2024)
This study investigates the impact of scholarships on student achievement at the Faculty of Education, State University of Surabaya. The research aims to describe the academic achievement of scholarship recipients, analyze their activities while receiving scholarships, examine the relationship between scholarship effectiveness and academic achievement, identify determinant factors influencing these relationships, and delineate academic criteria for scholarship eligibility. The study employs a mixed-methods approach, combining qualitative conversations with students, parents, administrators, and scholarship program managers, and quantitative surveys of scholarship recipients and non-recipients. Surveys were administered through paper and electronic questionnaires to students in the Faculty of Economics and Business and the Faculty of Engineering. The findings are expected to provide systematic policy recommendations for determining scholarship amounts and emphasize the need for structured scholarship advice and counseling. The study holds significant implications for understanding the role of scholarships in enhancing student performance and guiding future scholarship programs, ultimately leading to improved graduation rates, grade point averages, and employability skills among scholarship recipients.